2022
DOI: 10.1227/neu.0000000000002022
|View full text |Cite
|
Sign up to set email alerts
|

Access Site Complications and Management of the Transradial Approach for Neurointerventions

Abstract: BACKGROUND:The transradial approach has increasingly been used for neurointerventions because of the improved safety profile compared with transfemoral. However, it is important to be aware of potential complications such as radial artery (RA) spasm, RA occlusion, pseudoaneurysm, extravasation, arteriovenous fistula, and wrist hematoma as well as their management. OBJECTIVE: To present our institution's experience with the prevention and management of local access site complications associated with the transra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“… 4 In the neurointerventional field, among 1524 TRA procedures, ACS occurred in only 1 case (0.1%). 2 Regardless of the low incidence, the possibility of postoperative ACS should be taken seriously because delayed diagnosis could result in permanent sequelae, including irreversible necrosis and nerve damage in addition to tissue damage. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 In the neurointerventional field, among 1524 TRA procedures, ACS occurred in only 1 case (0.1%). 2 Regardless of the low incidence, the possibility of postoperative ACS should be taken seriously because delayed diagnosis could result in permanent sequelae, including irreversible necrosis and nerve damage in addition to tissue damage. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 1 However, TRA, similar to TFA, might also cause major puncture-site complications, including radial artery (RA) extravasation, delayed RA occlusion, pseudoaneurysm, infection, acute compartment syndrome (ACS), and avulsion of the RA. 2 Among these, early diagnosis and treatment of ACS are particularly imperative, since delays in appropriate management can lead to permanent sequelae, such as irreversible necrosis, nerve injury, and tissue damage. 3 In the field of neurointervention, although several reports have documented the frequency of postoperative ACS, few have described the clinical course and how to rescue this critical situation.…”
mentioning
confidence: 99%
“…1,2 Reportedly, in the cerebrovascular field, the TRA is sufficient for completing examinations and neuroendovascular treatment, except in cases where definitive selection of the branches of the external carotid artery or left vertebral artery is necessary. [3][4][5] Recently, the distal radial artery approach (DRA), which involves puncturing the radial artery (RA) running through the anatomical snuffbox, has garnered attention as a less invasive approach. [6][7][8] An additional advantage is that there is minimal restriction of patient movement after the test.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Reportedly, in the cerebrovascular field, the TRA is sufficient for completing examinations and neuroendovascular treatment, except in cases where definitive selection of the branches of the external carotid artery or left vertebral artery is necessary. 35…”
Section: Introductionmentioning
confidence: 99%
“…10 Furthermore, RAS can cause rare but serious access site complications, such as perforation, dissection, eversion or avulsion of the radial artery, catheter/sheath entrapment, and forearm hematoma leading to compartment syndrome. 8,[11][12][13][14][15] Maintaining the radial artery patency is important because radial artery occlusion prevents future use of the radial artery for vascular access in interventional procedures, as a donor vessel in bypass surgery, or for the construction of an arteriovenous fistulae in patients with end-stage renal disease. 16,17 Rathore et al 5 showed that RAS and discomfort were significantly reduced in patients with hydrophilic-coated sheaths, with no difference between long or short sheaths.…”
mentioning
confidence: 99%